Comparing coal mine rehabilitation practices in Queensland, Australia with Wyoming, United States of America - Dunlop, J; Purtill, J; Kuchanur, M; Wendtland, K (Mine Closure 2024: 17th International Conference on Mine Closure, 2024)
This paper compares open cut coal mine rehabilitation practices in Queensland, Australia, with Wyoming in the United States of America (USA). The industry in these jurisdictions have some similarities (and differences) that provide for qualitative comparison of the respective progressive rehabilitation performance. Rehabilitation of areas disturbed during open cut coal mining present a significant challenge in both jurisdictions. Open cut coal mining in both areas underwent significant expansion in the late 70s and early 80s. The regulation of mine rehabilitation (known as reclamation in the USA) has been approached differently in the USA and Australia. The USA introduced national federal laws governing reclamation early on during the expansion of the coal mining industry in 1977 with the option for individual states to be responsible for their implementation (primacy). In Australia, the responsibility for regulating mine rehabilitation rests with each of the states and territories. In Queensland, varying laws have been used to govern the rehabilitation process over time, however, laws governing environmental management of mining were consolidated in the mid-90s and again strengthened more recently in 2018. This paper considers some of the key aspects of rehabilitation including financial assurance (bonding), final landforms including the requirement to backfill pits, groundwater management in alluvial zones and a comparison of the rates of mine rehabilitation reported in both jurisdictions. The information presented in this paper was compiled from site inspections of coal mines in Wyoming, meetings held between the Office of the Queensland Mine Rehabilitation Commissioner (QMRC), the Wyoming Department of Environmental Quality (WDEQ) and the Federal Office of Surface Mining Reclamation and Enforcement (OSMRE), in addition to a review of published guidance materials, government reports, and legislation from both jurisdictions. Wyoming uses a system of full cost bonding, compared with a pooled fund/bonding hybrid model in Queensland. A desire to release bonds appears to motivate the completion of the rehabilitation and surrender process in Wyoming. Similarly, the hybrid system in Queensland provides a reduction in annual rehabilitation liability once rehabilitation is completed. Although the framework allows for this, there are few examples where parts of mining leases have been rehabilitated and surrendered in Queensland. A key difference between jurisdictions is that the USA, including Wyoming, requires mine voids to be backfilled to their ‘approximate original contour’ (AOC). Although some voids may be backfilled or partially backfilled after mining in Queensland, most are likely to remain and are unlikely to sustain a viable use in the long-term. Wyoming also has noteworthy protections for surface and groundwater hydrology including alluvial valley floors regarded as important for agriculture. A comparison of progressive rehabilitation rates found that the proportion of rehabilitated land compared with the area of disturbance was substantially higher (two-fold) in Wyoming compared with Queensland. This comparison carries some assumptions and is subject to change over time. Further analysis of the issues and examples are given with a view to identifying opportunities for improving rehabilitation rates.
Keywords: coal mining; rehabilitation practices; progressive rehabilitation; Wyoming; Queensland